Cellular Immune Signal Exchange From Ischemic Stroke to Intestinal Lesions Through Brain-Gut Axis - Yang, Zizhao; Wei, Fei; Zhang, Bin; Luo, Yun; Xing, Xiaoyan; Wang, Min; Chen, Rongchang; Sun, Guibo; Sun, Xiaobo (Frontiers in Immunology, 2022)
As a vital pivot for the human circulatory system, the brain-gut axis is now being considered as an important channel for many of the small immune molecules’ transductions, including interleukins, interferons, neurotransmitters, peptides, and the chemokines penetrating the mesentery and blood brain barrier (BBB) during the development of an ischemic stroke (IS). Hypoxia-ischemia contributes to pituitary and neurofunctional disorders by interfering with the molecular signal release and communication and then providing feedback to the gut. Suffering from such a disease on a long-term basis may cause the peripheral system’s homeostasis to become imbalanced, and it can also lead to multiple intestinal complications such as gut microbiota dysbiosis (GMD), inflammatory bowel disease (IBD), necrotizing enterocolitis (NEC), and even the tumorigenesis of colorectal carcinoma (CRC). Correspondingly, these complications will deteriorate the cerebral infarctions and, in patients suffering with IS, it can even ruin the brain’s immune system. This review summarizes recent research on abnormal immunological signal exchange mediated polarization subtype changes, in both macrophage and microglial cells as well as T-lymphocytes. How gut complications modulate the immune signal transduction from the brain are also elucidated and analyzed. The conclusions drawn in this review could provide guidance and novel strategies to benefit remedies for both IS and relative gut lesions from immune-prophylaxis and immunotherapy aspects.